Frequency-Domain Packet Combining Techniques for UWB - Silva, Mário Marques da (2017)
Ultrawideband (UWB) technology uses extremely wide bandwidth signals with low power spectral density. This approach fundamentally changes the wireless communications paradigm because the large signal bandwidth leads to the emergence of some interesting and unique channel properties [Allen et al. 2006] [Sipal et al. 2012]. There has been an enormous interest in the technology over the last twenty years because UWB, and specifically UWB MIMO, enables very high-rate wireless communications, wireless asset localization, and microwave medical imaging, with properties and capabilities unmatched by conventional wireless technologies. The objective of the chapter is to introduce UWB MIMO technology and to provide an overview of its major potential and constraints for these three fields.